Artificial Intelligence-Assisted Learning Videos for Biotechnology Instruction: Effects on Senior High School Students' Learning Outcomes - Rieke Octaviani Aritonang; Eko Prasetya (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study examined the effect of Artificial Intelligence (AI)-assisted learning video on the biotechnology learning outcomes of senior high school students. A quantitative approach was employed using a quasi-experimental, pretest-posttest control group design, involving an experimental class and a control class at High School 1 Labuhan Deli, Indonesia, each consisting of 30 students (N = 60). Learning outcomes were measured using 15 multiple-choice items selected from an initial pool of 30 items covering cognitive levels C1 to C6 of Bloom's Taxonomy, following item-trial procedures encompassing validity, reliability, discrimination index, and difficulty level. Data was analyzed using tests of normality and homogeneity, followed by a paired-sample t-test. The pretest results indicated comparable baseline ability between the control (M = 47.11) and experimental (M = 45.78) groups. After treatment, the experimental group's posttest mean (M = 89.55) was considerably higher than that of the control group (M = 72.00), corresponding to mean gains of 43.77 and 24.89 points, respectively. Hypothesis testing confirmed a statistically significant difference between groups (t = 7.03 > t-table = 2.00; p = 0.000 < 0.05). The largest gains in the experimental group occurred on indicators related to the utilization of microorganisms, tissue culture, and cloning and genetic engineering, suggesting that AI-assisted video is particularly effective for visualizing abstract, microscopic biological processes. These findings indicate that AI-assisted learning video is a more effective instructional medium than conventional lecture-and-textbook teaching for biotechnology content, and broader adoption of such media is recommended for similarly abstract topics in biology education.